Mechanistics of secretome proteins from Paenibacillus polymyxa Kp10 and Lactococcus lactis Gh1 against methicillin-resistant Staphylococcus aureus and Vancomycin-resistant enterococcus - Zainal Baharin, Nurul Hana (2023)
Resistance in pathogenic bacteria has emerged as a major global public health concern. Antibiotic-resistant bacterial infections are a major cause of patient mortality and morbidity, and rising antibiotic resistance is seriously compromising the vast medical advances made possible by antibiotics over the last decade. Hence, alternative approaches in controlling the bacterial infections are urgently needed. Paenibacillus polymyxa Kp10 (Kp10) and Lactococcus lactis Gh1 (Gh1) both are bacterial isolates that were believed to exhibit antimicrobial activity. Therefore, the effectiveness of secretome protein extracts isolated from Kp10 and Gh1 as the therapeutic agent in the treatment against antibiotic-resistant bacterial strains, namely, vancomycin-resistant Enterococcus (VRE) and methicillin-resistant Staphylococcus aureus (MRSA) were investigated. The main objective of this study is to determine the inhibition mechanisms of secretome protein extracted from Kp10 and Gh1 against MRSA and VRE bacteria. Minimal Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and timeto- kill assays were used to determine the sensitivity and viability of MRSA and VRE bacterial cells following treatment with the secretome proteins of Kp10 and Gh1. Next, to determine the morphological changes of MRSA and VRE after treated with Kp10 and Gh1, the microscopic analysis using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were observed. Then, to elucidate the antimicrobial mechanism of secretome protein of Kp10 and Gh1 against MRSA and VRE, 2D gel and sonication proteomic analysis based on time dependent manner by using liquid chromatography-mass spectrometry (LCMS) were run by comparing upregulated and downregulated proteins. Subsequently, the proton motive force study included the efflux of ATP; the pH gradient and the membrane potential study in treated MRSA and VRE were conducted. The differential proteins expression in MRSA and VRE treated with secretome proteins Kp10 and Gh1 in time dependent manner were analyzed. Protein extracts were obtained from treated MRSA and VRE cells by sonication and the protein profiling were identified by using liquid chromatography-mass spectrometry (LCMS). The safety of both secretome proteins in human cell also were evaluated by the characterization of serum stability towards secretome proteins and their potential toxicity towards Medical Research Council cell strain 5 cell (MRC5), a kind of human lung cells. MRSA and VRE bacteria that were found to be sensitive to secretome proteins of Kp10 and Gh1 were treated with the respective secretome protein extract and were found to display several distinguished and apparent signs of morphological and internal composition changes, based on the microscopic analysis. Several proteins that were found to be important in cell wall functions and cell division, cell wall biosynthesis/ protein synthesis and the stress response were identified to be down-regulated or upregulated in both treated cells without changing the membrane potential gradient. Next, the cytotoxicity test suggested that there were no cytotoxic effects have been observed on both secretome proteins when treated on MRC5 cells. Hence, there is no IC50 was determined. Finally, the preliminary test on the effect of secretome proteins in human serum was done using the agar well diffusion method. From this study, there are no significant changes in the inhibition zone of secretome proteins in serum when treated on the bacterial strain, thus giving the initial impression that peptide is safe to use in the human body. In conclusion, secretome proteins of Kp10 and Gh1 were demonstrated to reduce the growth number of VRE and MRSA by damaging the cell membrane, suggesting that both secretome proteins may serve as a potential therapeutic agent for antibiotic-resistant pathogen.